The Micro Small-Level Enterprises (MSES) and Cooperatives in Presidential Regulation Number 12 of 2021: Assessing The Potential Of Corruption Toward Changes In Government Procurement Policy For Micro Small-Level Enterprises (MSEs) And Cooperatives In Presidential Regulation Number 12 Of 2021 Concerning Amendment To Presidential Regulation Number 16 Of 2018 Concerning Government’s Procurement Of Goods And Services - Ferdinand, Adam Khafi; Amrullah, Rinaldy (JASSP, 2021)
Presidential Regulation Number 12 of 2021 concerning amendment the Presidential Regulation Number 16 of 2018 (Presidential Regulation 12/2021) was the government efforts for micro small-level enterprises (MSEs) and cooperatives to be involved in the public procurement of goods and services. However, it still needs to be anticipated because there are always irregularities that usually occur, namely corruption. This research aims to determine how the amendment of the public procurement regulation in the Presidential Regulation 12/2021 especially for MSEs and cooperatives, and also how to assess the Presidential Regulation 12/2021 can reduce the potential for corruption in the process of public procurement. This research uses a normative method with a comparative approach and a statutory approach. The results of this research indicate the Presidential Regulation 12/2021 are the elimination of medium-level enterprises, the government's obligation to allocate a minimum budget of 40%, and also increase the budget ceiling for MSEs and cooperatives up to IDR 15 billion. E-Procurement for MSEs and cooperatives still has the potential for corruption, but with the new policy in the form of competency certification, and if there is an increase in regulations from the National Procurement Board (LKPP) in terms of provider qualifications, procurement can produce quality and efficient products. Keywords: Cooperatives, Potential of Corruption, Presidential Regulation 12/2021, Government’s Procurement Goods and Services, Small-Level Enterprises (MSEs)